2007
DOI: 10.1111/j.1745-4530.2007.00111.x
|View full text |Cite
|
Sign up to set email alerts
|

OPTIMIZING ELECTRON BEAM IRRADIATION OF “TOMMY ATKINS” MANGOES (MANGIFERA INDICA L.)

Abstract: We determined the optimum irradiation treatment for decontamination of physiologically mature fresh "Tommy Atkins" mangoes, without PRACTICAL APPLICATIONSThis study shows that precise irradiation treatment of fruits such as mangoes is required to ensure the entire product is exposed to the target dose.3 Corresponding

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 19 publications
2
9
0
1
Order By: Relevance
“…Irradiation increased (P < 0.05) the respiration rate (CO 2 production) (P < 0.05) of the broccoli. The same behavior was observed in other fresh produce undergoing irradiation treatment such as lettuce, citrus, mango, and blueberry (Han et al, 2004;Landaniya, Singh, & Wadhawan, 2003;Moreno et al, 2006aMoreno et al, , 2006bMoreno, Castell-Perez, Gomes, Da Silva, Kim, & Moreira, 2007; …”
Section: Respiration Ratesupporting
confidence: 76%
See 1 more Smart Citation
“…Irradiation increased (P < 0.05) the respiration rate (CO 2 production) (P < 0.05) of the broccoli. The same behavior was observed in other fresh produce undergoing irradiation treatment such as lettuce, citrus, mango, and blueberry (Han et al, 2004;Landaniya, Singh, & Wadhawan, 2003;Moreno et al, 2006aMoreno et al, , 2006bMoreno, Castell-Perez, Gomes, Da Silva, Kim, & Moreira, 2007; …”
Section: Respiration Ratesupporting
confidence: 76%
“…Irradiation has proven to be an effective treatment for many fresh produce, particularly electron-beam irradiation (CastellPerez, Moreno, Rodriguez, & Moreira, 2004;Han, Gomes-Feitosa, Castell-Perez, Moreira, & Silva, 2004;Moreno, Castell-Perez, Gomes, Da Silva, & Moreira, 2006a, 2006bMoreno, Castell-Perez, Gomes, Da Silva, Kim, & Moreira, 2007). The advantages of this technology are high lethality, great penetration into the product core, cold application (i.e., does not increase product temperature) and, negligible quality detrimental effects, when applied properly.…”
Section: Introductionmentioning
confidence: 98%
“…Irradiation dose at 0.25 kGy and LDPE pouches was found to maintain highest total sugar content in juice at zero day. Moreno et al (2007) also reported reduction in total sugar content on irradiation at medium doses (1.5 kGy) in mango fruit. A significant decrease (P [ 0.05) in total sugar content of juice was observed when it was stored at room and low temperature.…”
Section: Total Sugarsmentioning
confidence: 91%
“…Earlier studies at lower doses were effective in preventing emergence of adult S. mangiferae and the beetles were sterilised at even lower doses (Seo et al 1973;Heather and Corcoran 1992;Follett 2001). At doses higher than 150 Gy, mango fruit quality was impaired (Moreno et al 2007).…”
Section: Quarantine and Phytosanitary Measuresmentioning
confidence: 99%